2020
DOI: 10.12973/ijem.6.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Digital Literacy and Metaphoric Perceptions of Teacher Candidate

Abstract: The aim of this study was to investigate the digital literacy skills and metaphorical perceptions of teacher candidates. The mixed approach has been used in the analysis. The quantitative dimension of the study consists of the "Digital Literacy Scale" scores collected from the teacher candidates, and the qualitative component is made up of the metaphors they have developed about the definition of digital literacy. The study was carried out with 297 prospective teachers who are pursuing their education at the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…There is also an urgent need for curricular revisions to increase contact and familiarity in signature pedagogies. New findings on perceptions of digital literacy highlight that despite strong belief in its vitality for their teacher development, many prospective teachers still continue to associate digital literacy with complexity (Dedebali, 2020). In today's world, where the focus has recently shifted in higher education from digital literacy to digital fluency (a much more sophisticated competence to use digital tools for content co-creation, creative design, and adaptive problemsolving), the teacher is no longer conceived as knowledge-transmitter but rather facilitator and curator, and the overwhelming necessity of redesigning instruction accordingly (i.e.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…There is also an urgent need for curricular revisions to increase contact and familiarity in signature pedagogies. New findings on perceptions of digital literacy highlight that despite strong belief in its vitality for their teacher development, many prospective teachers still continue to associate digital literacy with complexity (Dedebali, 2020). In today's world, where the focus has recently shifted in higher education from digital literacy to digital fluency (a much more sophisticated competence to use digital tools for content co-creation, creative design, and adaptive problemsolving), the teacher is no longer conceived as knowledge-transmitter but rather facilitator and curator, and the overwhelming necessity of redesigning instruction accordingly (i.e.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…That means Innovation and technology are changing the world and our daily lives. (Dedebali, 2020) In addition, if viewed from the awareness of the development of teachers in schools under the local administrative organization of Thailand, it was found that there was a policy to develop outstanding leadership for teachers based on the main components, sub-elements, and the indicators used in this research are also. year National Strategy and the Thailand 4.0 Strategy, where teachers of all levels and types of education were developed in accordance with professional standards for quality assurance and teacher professional competency standards and the educational quality assurance system (Office of the Education Council Secretariat, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…Digital media literacy in students of prospective teacher is crucial and urgent to consider. It requires unlimited tutoring guidance [28]. The learning constructs of students of prospective teacher offer constructive pedagogy, freedom, and courage to learn and foster meaning in digital literacy.…”
Section: Students Learning Constructions Based On Digital Media Literacymentioning
confidence: 99%